A função social da poesia e o seu lugar no cotidiano profissional da assistente social - Silva, Juliana Garcia de Brito de Lima e (2023)
The study object for this presentation is the social function of poetry and its place in the professional routine of social workers. Qualitative field research, supported by the methodology of "research-action" proposed by René Barbier, the author who presents the technical instrument "journey of roaming," was realized as a data collection tool to deepen the proposed object. In order to capture the narratives written in these diaries, the concept of "writing" was used as proposed by the writer Conceição Evaristo. The study consists of theoretical-scientific references from Marxist authors who debate the social function of poetry, such as Carlos Felipe Moises, and sources from literary works of diverse genres, by writers such as Lygia Fagundes Telles. The work contains an introduction, three chapters that complete its development, and final considerations. The first chapter discusses the dimension of affection evidenced in the poetic writing of one of the participants, who manifests an intense relationship with the profession, and the people assisted in her daily life. The second chapter will highlight the "poetry of everyday life" revealed in the writings of the other two participants who explore the "look and listen" as places of fertile soil for using poetry to mediate professional actions. The third chapter will present, through writing in the first person, the researcher's writing. Fourteen poems, short stories, and letters texts will be exposed and organized in "Estações da Via Mestra," which mentions the path taken during the master's course in the Graduate Program in Social Work at PUC-SP. The final considerations bring a reflection between freedom, a principle foreseen in the professional code of ethics of the social worker, and the poetic state, which contributes to the expansion of the present theme where it approaches poetry as a powerful resource for the development of essential attributes for advances and daily confrontations and the embrace of a new societal project trodden in the daily life of professional social workers